2003
DOI: 10.1007/bf02983783
|View full text |Cite
|
Sign up to set email alerts
|

Absence of R24C Mutation of the CDK4 Gene in Leukemias and Solid Tumors

Abstract: A mutation of the p16(INK4a)-binding domain of the cyclin dependent kinase 4 (CDK4) gene, R24C, has been reported in some cases of melanoma. This mutation prevented binding of the CDK4 inhibitor p16(INK48) to CDK4. To determine the relevance of the mutation, we performed polymerase chain reaction-single-strand conformation polymorphism (PCR-SSCP) analysis in diverse types of human leukemias and solid tumors. No mobility shifts indicating sequence alterations were observed in 273 tumors and 49 cell lines from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…However, the causal role of these alterations in tumor development is difficult to assess [25]. Present study revealed that there was no germline mutation in codon 24 and 22 of CDK4 and these results support the findings of previous studies [20,26,27]. The potentially dominant Arg24Cys mutation of CDK4 was not detected in Indian patients with squamous cell carcinoma of head and neck [8].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, the causal role of these alterations in tumor development is difficult to assess [25]. Present study revealed that there was no germline mutation in codon 24 and 22 of CDK4 and these results support the findings of previous studies [20,26,27]. The potentially dominant Arg24Cys mutation of CDK4 was not detected in Indian patients with squamous cell carcinoma of head and neck [8].…”
Section: Discussionsupporting
confidence: 88%
“…A prior study found that mutations that decreased cyclin binding of CDK4 by greater than 80% also decreased kinase activity [19]. Generally, the level of cyclin binding of the various CDK4 mutants correlates well with kinase activity, and the sequences involved in p16 INK4a binding are a subset of those involved in cyclin D1 binding [20]. Figure 3 shows In silico structural model analysis of CDK4 protein using the UCSF Chimera 1.5.3 program revealed that Ser52Thr and Glu67Gln mutations are located in N terminal domain contain αC helix (aa 1–96).…”
Section: Discussionmentioning
confidence: 99%
“…For more details see [79]. in many other types of human neoplasms the R24C CDK4 mutation could not be detected [98,99], and so far, no kinase activating mutations have been identified in CDK2 [100,101].…”
Section: Rb/e2f and Melanomamentioning
confidence: 94%
“…However, several laboratories have been unable to identify the same mutations in other types of cancers including solid tumors, leukaemia and tumor-derived cell lines [38][39][40][41].…”
Section: Cdk4mentioning
confidence: 98%